Feeding practices and growth of infants with Pierre Robin Sequence. (March 2019) - Dorise, Bonnie; Trivedi, Amit; Galea, Claire; Walker, Karen; Mehta, Bhavesh
Abstract: Objectives: To assess the impact of feeding practices on growth in infants with Pierre Robin Sequence (PRS) during their inpatient stay in a neonatal intensive care unit in a large tertiary paediatric hospital setting. Methods: A retrospective review of feeding practices in infants with PRS was conducted between January 2006 and September 2017. Baseline demographics, nutrition-related and general outcomes were collected. Feeding difficulties, length of stay (LOS) and malnutrition were the primary outcome measures. Feeding difficulties included absence or poor-quality suck, episodes of aspiration, use of proton pump inhibitors or multiple episodes of vomiting. Malnutrition was classified as a weight-for-age Z score of < -1. Results: Analysis was conducted on 49 infants with PRS that met eligibility criteria. Feeding difficulties correlated with a longer LOS (24.1 vs 6.8 days ( p  = 0.001)) Z-scores differed significantly between birth and discharge (0.21(1.84) vs −1.27(2.14)) ( p  < 0.001*) with malnutrition being evident in 26 infants of which only 17 infants were seen by a dietitian. Presence of intrauterine growth restriction (IUGR) increased the likelihood of malnutrition (OR 1.40(CI-1.11–1.77)). Conclusion: Infants with PRS are highly likely to have feeding difficulties and malnutrition. Early intervention by a dietitian is recommended to reduce the impacts of feeding difficulties, meet elevated energy requirements and facilitate growth. Infants with a longer inpatient stay or presence of IUGR should have their growth and feeding routinely monitored.